THE EFFECTS OF HOLIDAYS ON THE GHANAIAN EQUITY MARKET - Kudjawu, Alexandra Fafali; Andoh, Charles; Kuttu, Saint (Machakos University, 2019)
This paper sought to determine if the Ghanaian equity market is a semi-strong efficient market by investigating whether or not the holiday effect exists by adopting an ARMAX (2, 2) - GARCH (1, 1) model with 𝐺𝐿+ innovation. The results show that there are significant positive pre-holiday and post-holiday effects which may not be as a result of bearing higher levels of risk. This finding is important to investors to assist strategise better in order to take advantage of this calendar anomaly discovered on the Ghanaian equity market.
Keywords: ARMAX; Calendar anomalies; Efficient market hypothesis; GARCH; 𝐺𝐿+ innovation; Holiday effect